Asean Economic Dynamics: An Analysis of The Impact of Trade Openness, Foreign Direct Investment, and Export on Economic Growth - Lestari, Ajeng; Muhdir, Ibnu; Ashari, Nesha Rizky (Jurnal Ekonomi Pembangunan, 2024)
This study aims to explain economic growth in ASEAN countries. The variables that affect the economic growth rate are trade openness, foreign direct investment, and exports. This study uses secondary data from the World Bank and UNCTAD. The data is annual data from 2018-2022. The analytical tool used is the Vector Error Corrections Model (VECM), which uses a unit root test, optimal lag test, cointegration test, and VECM model. The results show that trade openness, FDI, and exports affect economic growth in the short-term analysis, but FDI and exports hurt economic growth. In the long run, the results of this study indicate that trade openness does not affect economic growth. At the same time, FDI significantly affects economic growth in ASEAN countries, and exports do not affect economic growth in 2018- 2022.